2022
DOI: 10.33225/jbse/22.21.351
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Gender, Across School-Type on Upper-Secondary Students’ Development of Experimental Reasoning on Organic Qualitative Analysis

Abstract: Chemical tests (qualitative analysis) on functional groups may improve students’ understanding of basic concepts about the structure of organic compounds and their reactivity. However, upper-secondary school students have difficulties in learning organic qualitative analysis. This research has studied whether the gender of students and school-type affect development of experimental reasoning on organic qualitative analysis. From three school-types, 50.2% males and 49.8% females were sampled through a multistag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…This study has also revealed that, difficult and abstract nature of concepts affect how that concept is been taught by teachers and learned by students. This is due to that fact that, organic qualitative analysis has been found difficult to teachers (Anim-Eduful & Adu-Gyamfi, 2021) and also to students (Adu-Gyamfi, & Anim-Eduful, 2022). Furthermore, this study has revealed that teaching and learning chemistry concepts such as organic qualitative analysis should be practical oriented.…”
Section: Discussionmentioning
confidence: 87%
“…This study has also revealed that, difficult and abstract nature of concepts affect how that concept is been taught by teachers and learned by students. This is due to that fact that, organic qualitative analysis has been found difficult to teachers (Anim-Eduful & Adu-Gyamfi, 2021) and also to students (Adu-Gyamfi, & Anim-Eduful, 2022). Furthermore, this study has revealed that teaching and learning chemistry concepts such as organic qualitative analysis should be practical oriented.…”
Section: Discussionmentioning
confidence: 87%
“…OQA is a concept in organic chemistry that helps students understand the fundamental concepts of the structure and reactivity of organic compounds (Adu-Gyamfi & Anim-Eduful, 2022). Learning of chemical properties and reactions of organic compounds is abstract, difficult, and complicated (Vishnoi, 2009) for students to learn.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have revealed that students have difficulties in many of these concepts in organic chemistry. For instance, concepts of nomenclature of organic compounds using IUPAC system by (Adu-Gyamfi et al, 2013, organic reactions and mechanisms (Bhattacharyya & Bodner 2005;Ferguson & Bodner, 2008;Graulich, 2015;Tang et al, 2010;Wasacz, 2010) functional groups detection (Adu-Gyamfi & Anim-Eduful, 2022;Anim-Eduful & Adu-Gyamfi, 2021, 2022b. For example, we reported in our study (Anim-Eduful & Adu-Gyamfi 2022b) that senior high school (SHS) chemistry students demonstrated conceptual difficulties at a level of no scientific understanding in the detection of organic functional groups such as hydrocarbons (such as alkenes, alkynes, and benzene), alkanols, alkanoic (carboxylic) acids, alkylalkanoates (esters), alkanals (aldehydes), alkenones (ketones) and amides using a two-tier diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations